Proceedings of the 7th International Conference on Electronic Commerce - ICEC '05 2005
DOI: 10.1145/1089551.1089589
|View full text |Cite
|
Sign up to set email alerts
|

A web trust-inducing model for e-commerce and empirical research

Abstract: Trust is critical to the success of e-commerce. Despite the richness of e-trust literature, it is lack of empirical research on this area. So in this paper, we made a review on the e-commerce trust studies, both the literature and empirical studies. Basing on relevant trust literatures we presented a web trust-inducing model and proposed four hypotheses. This model consists of four dimensions, namely graphic design, structure design, content design and social-cue design. In order to test the original model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In their 'call to arms', Marsh and Meech [22] challenged website designers to start thinking about how trust can be facilitated in the initial ('grabbing') stages of online engagement, claiming that websites can be designed in such a way that trust is an integral part of the design rather than an afterthought. Several researchers have indeed considered the components and structure of an e-Commerce website design that might induce trust in consumers (e.g., [1,2,4,5,8,13,15,32,36,39]). Factors such as branding, ease of use, professional look-and-feel, website structure, channels available for communication with the vendor, privacy, policies, and third party assurance mechanisms have been collectively recognized as being essential to consumers' assessment of trust.…”
Section: Trust and Website Designmentioning
confidence: 99%
See 4 more Smart Citations
“…In their 'call to arms', Marsh and Meech [22] challenged website designers to start thinking about how trust can be facilitated in the initial ('grabbing') stages of online engagement, claiming that websites can be designed in such a way that trust is an integral part of the design rather than an afterthought. Several researchers have indeed considered the components and structure of an e-Commerce website design that might induce trust in consumers (e.g., [1,2,4,5,8,13,15,32,36,39]). Factors such as branding, ease of use, professional look-and-feel, website structure, channels available for communication with the vendor, privacy, policies, and third party assurance mechanisms have been collectively recognized as being essential to consumers' assessment of trust.…”
Section: Trust and Website Designmentioning
confidence: 99%
“…Amongst these, we looked for agreement on the validity of trust triggers. Yang et al [39], Jarvenpaa et al [15], and Akhter [1] verified that availability of customer testimonials and feedback is important when attempting to engender consumer trust. Yang et al [39] and Akhter [1] confirmed that user-friendly interface design and navigation, and readily available information on the vendor's processes and policies, trigger development of trust amongst consumers.…”
Section: Trust Triggersmentioning
confidence: 99%
See 3 more Smart Citations